Evaluation of a Multiplex PCR Assay with Molecular Beacon Probes to Rapidly Detect Bacterial Pathogens Directly in Bronchial Alveolar Lavage (BAL) Samples from Patients with Hospital-Acquired Pneumonia (HAP). (4th October 2017) - Chavda, Kalyan D; Satlin, Michael; Chen, Liang; Chavda, Bhakti; Manca, Claudia; Westblade, Lars; Jenkins, Stephen G; Walsh, Thomas J; Kreiswirth, Barry N
Abstract: Background: Bacterial pneumonia is a common complication in hospitalized patients and it is associated with high morbidity and mortality. Standard culture-based methods may take 2–3 days to identify the etiologies of HAP, leading to delays in appropriate therapy. A rapid molecular assay that could diagnose the etiology of bacterial pneumonia directly from BAL samples within a few hours could facilitate faster and more directed administration of antimicrobial therapy. Methods: BAL samples were collected from hospitalized patients with suspected pneumonia, including ventilated patients, from December 2016 through April 2017. Genomic DNA was isolated from BAL samples using NucliSENS ® easyMAG ® . A panel of target-specific molecular beacon probes in a real time PCR assay (MB-PCR) was used to identify the following pathogens: universal bacterial Identification (16S rRNA), E. coli ( uidA ), K. pneumoniae ( gapA ), S. aureus ( spa ), P. aeruginosa ( rpsL ), A. baumannii (Ab-ITS) and the following resistance determinants: ESBLs (CTX-M, TEM and SHV), carbapenemases (NDM, VIM, IMP, OXA-48 and KPC) and mec A. The results of MB-PCR were then compared with quantitative culture results performed by the clinical microbiological lab. Results: We evaluated 53 BAL samples to identify the bacterial pathogen and key resistance determinants. Thirty-one samples yielded growth of ≥1 × 10 4 CFU/mL of bacteria by quantitative culture. The bacterial identification using MB-PCR for 16S rRNA correctly identified the presence of bacteria in all 31 samples (100% sensitivity). The MB-PCR identified P. aeruginosa ( n = 5), S. aureus ( n = 5), E. coli ( n = 1), A. baumannii ( n = 1), and K. pneumoniae ( n = 1) in BAL samples that yielded ≥1 × 10 4 CFU/mL of the same pathogen by culture (100% sensitivity). The MB-PCR also identified bla TEM -harboring E. coli that grew ampicillin-resistant E. coli by culture. The specificity of the16S rRNA probe was 70%, as 7/53 BAL were false positive, whereas the specificity for the MB-PCR was 100% for P. aeruginosa, S. aureus, E. coli, and A. baumannii, and 98% for K. pneumoniae . Conclusion: Multiplex MB-PCR assay is a rapid, sensitive and specific tool for detection of common bacterial causes of nosocomial pneumonia and important resistance determinants directly from BAL samples. Disclosures: M. Satlin, Hardy Diagnostics: Investigator, Research support; S. G. Jenkins, Cormedix: Consultant, Consulting fee; Bayer: Consultant, Consulting fee Merck: Grant Investigator and Scientific Advisor, Research grant;   T. J. Walsh, The Medicines Company: Consultant and Investigator, Consulting fee and Research grant Astellas: Consultant and Investigator, Consulting fee and Research grant Allergan: Consultant and Investigator, Consulting fee and Research grant Merck: Consultant and Investigator, Consulting fee and Research grant